2008
DOI: 10.1021/bi8012406
|View full text |Cite
|
Sign up to set email alerts
|

Using an Amino Acid Fluorescence Resonance Energy Transfer Pair To Probe Protein Unfolding: Application to the Villin Headpiece Subdomain and the LysM Domain

Abstract: Previously, we have shown that p-cyanophenylalanine (PheCN) and tryptophan (Trp) constitute an efficient fluorescence resonance energy transfer (FRET) pair that has several advantages over commonly used dye pairs. Here, we aim to examine the general applicability of this FRET pair in protein folding–unfolding studies by applying it to the urea-induced unfolding transitions of two small proteins, the villin headpiece subdomain (HP35) and the lysin motif (LysM) domain. Depending on whether PheCN is exposed to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 52 publications
4
71
0
Order By: Relevance
“…The method will be easiest to interpret quantitatively in terms of helix formation when the F CN group is exposed to solvent in both states since the fluorescence quantum yield is influenced by hydrogen bonding to the cyano group as well as by quenching from other protein side-chains. If the F CN group were buried in one conformation, but not in the other, then the observed intensity change would be a convolution of the effects due to changes in side-chain quencher interactions and the effects of changes in solvation (18). However, note that both quenching and side-chain burial reduce F CN fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The method will be easiest to interpret quantitatively in terms of helix formation when the F CN group is exposed to solvent in both states since the fluorescence quantum yield is influenced by hydrogen bonding to the cyano group as well as by quenching from other protein side-chains. If the F CN group were buried in one conformation, but not in the other, then the observed intensity change would be a convolution of the effects due to changes in side-chain quencher interactions and the effects of changes in solvation (18). However, note that both quenching and side-chain burial reduce F CN fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…HP35 folds fast (∼1 μs) compared to large proteins, allowing tractable folding/unfolding simulations. Consequently, it has served as a model system in a number of computational folding studies (3)(4)(5), as well as a variety of experimental studies (6)(7)(8). NMR and X-ray diffraction studies have indicated that wild-type HP35 folds into three alpha helices ( Fig.…”
mentioning
confidence: 99%
“…However, Kayser et al found it to be a particularly useful tool for studying structure-function relationships in monoclonal antibodies, which were found to have an unusually high Trp content [199]. Another use of Trp as a natural fluorophore for FRET is to probe protein folding/unfolding, an important yet poorly understood biological process [200][201][202]. For example, Jha et al used FRET to study the unfolding of a small protein, monellin [202].…”
Section: Natural Fluorophoresmentioning
confidence: 99%
“…The photophysics of this useful nonnatural amino acid has recently been characterized [211,215]. The Trp-PheCN FRET pair has been used to determine detailed protein folding and unfolding in two small proteins, the villin headpiece subdomain (HP35) and the lysin motif (LysM) domain [200]. Two other nonnatural amino acids, 7-azatryptophan (7AW) and 5-hydroxytryptophan (5HW) ( Figure 6.13), were recently found to be FRET acceptors to PheCN [210].…”
Section: Nonnatural Amino Acidsmentioning
confidence: 99%